Do Judicial Instructions Aid in Distinguishing Between Reliable and Unreliable Jailhouse Informants? - Wetmore, Stacy A. (Criminal justice and behavior, 2020)
Jailhouse informants are a leading cause of wrongful convictions. In an attempt to preempt such miscarriages of justice, several states (e.g., Connecticut and California) have mandated that judicial instructions be provided to act as a safeguard against false testimony. This study evaluated the effectiveness of these instructions in helping jurors distinguish between reliable and unreliable jailhouse informants. Participants read a trial transcript that varied instructions (Standard, Connecticut, Enhanced) and informant reliability (reliable, unreliable). The results indicated that the instructions had no effect on verdict decisions. Even though verdicts did not vary, participants rated the unreliable informant as less trustworthy, honest, and interested in justice than the reliable informant. This is consistent with previous findings that indicate that participants are aware of the legal prescriptions given in the instructions, but they do not implement them in making decisions. Therefore, instructions may be an insufficient safeguard.